2015
DOI: 10.2474/trol.10.262
|View full text |Cite
|
Sign up to set email alerts
|

Main Chain Effects in Tetraol-Functionalized Perfluoropolyethers

Abstract: The interfacial properties of perfluoropolyether (PFPE) films having the [(CF 2 ) n O] main chain with n = 1.5, 3 and 4, were systematically compared on carbon surfaces. The monolayer thickness decreases with increasing n, indicating that stiffer chains (larger n) lie flatter on the surface. The surface energy-derived disjoining pressure also increased with increasing n. Spin-stand tribological experiments indicated that clearance (slider-disk spacing) increased and PFPE lubricant pick-up decreased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This characteristic difference between D-4OH and Z-tetraol was observed previously [14] and is verified in the current study. Waltman reported that the flexibility of the lubricant molecules, Fomblin and Demnum, depends on their main chain structure [4]. Therefore, the difference in effective Young's modulus obtained in this study can be attributed to the flexibility of the two lubricant molecules.…”
Section: Young's Modulus Of D-4oh Lubricant Filmsmentioning
confidence: 50%
See 1 more Smart Citation
“…This characteristic difference between D-4OH and Z-tetraol was observed previously [14] and is verified in the current study. Waltman reported that the flexibility of the lubricant molecules, Fomblin and Demnum, depends on their main chain structure [4]. Therefore, the difference in effective Young's modulus obtained in this study can be attributed to the flexibility of the two lubricant molecules.…”
Section: Young's Modulus Of D-4oh Lubricant Filmsmentioning
confidence: 50%
“…To further increase the HDD capacity, it is necessary to decrease the PFPE lubricant film thickness to reduce the flying height of the magnetic head. Therefore, lubricants with various main-chain and end-group structures have been studied [1][2][3][4][5]. The properties of these lubricants are evaluated primarily on the basis of bonded ratio and surface energy, focusing on the adsorption conditions of the lubricant film; heat resistance, focusing on the evaporation property and decomposition at high temperature; molecular mobility, focusing on the replenishment property of the lubricant film; monolayer thickness, focusing on the physical thickness on the disk; and the properties that are evaluated in actual hard disk drives, such as lubricant pickup by the head slider.…”
Section: Introductionmentioning
confidence: 99%
“…End-functionalized linear perfluoropolyethers (PFPEs) have long served rigid magnetic media as the boundary lubricant of choice for tribological robustness related to head wear and contamination in the hard disk drive (HDD) [1][2][3]. During the last decade, several significant changes to the HDD have imposed on the chemical design of future boundary lubricant films.…”
Section: Introductionmentioning
confidence: 99%